Visceral adiposity indicators as predictors of metabolic syndrome in postmenopausal women - ANIK İLHAN, GÖKÇE (GALENOS YAYINCILIK, 2019)
Objective: The aim of the present study was to evaluate the importance of visceral adiposity indicators on metabolic parameters in postmenopausal women. Materials and Methods: This cross-sectional study included 200 postmenopausal subjects. Postmenopausal women were divided into two groups based on the presence of metabolic syndrome (MetS) as MetS+ and MetS-. Comparisons of clinical and metabolic characteristics were performed between the groups. Results: The current study included 200 postmenopausal women and 63 subjects were diagnosed as having MetS. Postmenopausal women with MetS demonstrated significantly higher values with respect to systolic and diastolic blood pressures, body mass index (BMI), waist-hip ratio (WHR), triglyceride (TG), lipid ratios, Homeostasis Model Assessment Insulin Resistance (HOMA) index, TG glucose (TyG), Visceral Adiposity Index (VAI), and lipid accumulation product (LAP) when compared with women without MetS. Correlation analyses showed that LAP and VAI were positively correlated with waist circumference, WHR, BMI, TG, lipid ratios, TyG and HOMA index, and with each other. LAP was also positively correlated with blood pressures. Conclusion: Visceral adiposity indicators may be useful as predictors of MetS in postmenopausal women.
Keywords: Menopause; metabolic syndrome; lipid accumulation product; visceral obesity; LIPID-ACCUMULATION PRODUCT; SUBCLINICAL ATHEROSCLEROSIS; ARTERIAL STIFFNESS; INSULIN-RESISTANCE; DISEASE; INDEX; SURROGATE; MARKERS; FAT